PTP Approach in Network Security for Misbehavior Detection - Rachna Pandey; Tripathi, Pradeep (IJRDO -Journal of Computer Science Engineering, 2020)
A PTP approach in network security for misbehavior detection system present a method for detecting malicious misbehavior activity within networks. Along with the detection, it also blocks the malicious system within the network and adds it to Blacklist. Malicious node defined as a compromised machine within the network that performs the task provided by bot server i.e. it does not forward the legitimate message to another node in the network or send some other message to a neighbor node. This system is based on Probabilistic threat propagation. This scheme is used in graph analysis for community detection. The proposed system enhances the prior community detection work by propagating threat probabilities across graph nodes. To demonstrate Probabilistic Threat Propagation (PTP) paper considers the task of detecting malicious node in the network. Proposed System also shows the relationship between PTP and loopy belief propagation.